When Peasants Enter the Scene: Brazil’s landless rural workers movement (MST) theatrical work and the interface with audiovisual language - Villas Bôas, Rafael Litvin; Canova, Felipe (Revista Brasileira de Estudos da Presença, 2022)
In this article it is analyzed the presence of peasants in the Brazilian theater, in a historical perspective from the pre-coup of 1964 until the recent period, in which connections were established between social movements like MST and political theater collectives and grassroots video. It is object of analysis in this paper the MST relations with these collectives and the places that the theatrical language started to occupy on MST, as well as the influences of several theatrical forms and the relation of this language with the audiovisual. The research seeks to highlight that the relation mediated by the socialization of the artistic means of production can replace the terms of the debate between theme and form: if the land can belong to everyone, art is also an inherent element of the human condition, not only relegated to those who specialized in the craft.